Paciente Femenina de 50 Años De Edad Con Hipertensión Arterial Estadío I - Olmedo Santana, Freddy Ramón (2018)
Hypertension is defined as a chronic, not transmissible disease that occurs due to the continuous increase and differential elevation of blood pressure in the arteries above normal values. The general objective was to determine a nutritional diet adapted to the needs of the patient. To develop the clinical case, an observational, transversal and descriptive methodology was used. Because the clinical history, food amnanesis, clinical examination and biochemical examinations were taken into account. The present case study is based on a female patient of 50 years of age, diagnosed with arterial hypertension stage I, which shows elevation of blood pressure (140/80 mm / hg), the comprehensive nutritional diagnosis of female patient is developed overweight with increased cardiovascular risk, related to genetic factor and bad eating habits evidenced by the increase in blood pressure and the 24-hour reminder which shows an excess consumption of carbohydrates, fats and salt. Finally, he made a personalized dietary plan with a low sodium diet of 1605 Kcal/ day, low in fat, high in fiber, divided into 5 meals. The case study is concluded by improving the nutritional status and lifestyle since a personalized diet was used to meet the needs of the patient.